Molecular Switching Behavior in Isosteric DNA Base Pairs. Issue 6 (20th February 2013) - Jissy, A. K.; Konar, Sukanya; Datta, Ayan
Abstract The structures and proton‐coupled behavior of adenine–thymine (A‐T) and a modified base pair containing a thymine isostere, adenine–difluorotoluene (A‐F), are studied in different solvents by dispersion‐corrected density functional theory. The stability of the canonical Watson–Crick base pair and the mismatched pair in various solvents with low and high dielectric constants is analyzed. It is demonstrated that A‐F base pairing is favored in solvents with low dielectric constant. The stabilization and conformational changes induced by protonation are also analyzed for the natural as well as the mismatched base pair. DNA sequences capable of changing their sequence conformation on protonation are used in the construction of pH‐based molecular switches. An acidic medium has a profound influence in stabilizing the isostere base pair. Such a large gain in stability on protonation leads to an interesting pH‐controlled molecular switch, which can be incorporated in a natural DNA tract.